Comparison of the Biochemical Composition of the Edible Part of Three Syrian Economic Marine Fish Species Belonging to the Family of Mugilidae - بدران, معينة; حامد, فاتن; خضور, سدير (Latakia University Journal -Basic Sciences Series, 2021)
This research aims to compare the biochemical composition (protein, lipid) of the edible portion for three local species belonging to Mugilidae family. Mugil cephalus, Liza aurata, and Chellon labrosus. Fish samples were collected from two different sites on the coast of Tartous city: the marine area facing the estuary of Marqia river (Al-Khrab), and the marine area facing the estuary of Al-Abrash river (Al-Hamidiyah), during the winter and summer of 2020. Seasonal variation in biochemical composition of these species in both sites were studied. The results showed that the proportion of the protein and lipid percentages at the meat of these species were higher in Al-Hamidiyah site compared to Al-Kharab site, and The average value of protein in the two sites was during winter and summer for the specie Mugil cephalus (17.68±0.49%, 16.11±0.94%), Chellon labrosus (18.95±1.05%, 16.88±1.81%), and for Liza aurata (17.92±0.90%, 17.05±0.66%) respectively . As for the average value of fat of these species in both sites during the winter and summer seasons was respectively for Mugil cephalus (2.94±0.40%, 4.52±1.008%), Chellon labrosus (3.07±1.36%, 5.43±1.26%), and for Liza aurata (3.15±0.97%, 5.54±0.43%). As for the moisture and ash, the average of moisture was at the three types (76.20%), and the average of ash was (1.47%).